REDISCOVERING PANCASILA-BASED CIVIC EDUCATION THROUGH ARTIFICIAL INTELLIGENCE ETHICS: A FRAMEWORK FOR CHARACTER AND DIGITAL CITIZENSHIP TRANSFORMATION IN INDONESIA - Bambang Yuniarto (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study aims to formulate a conceptual framework for civic education grounded in Pancasila values ​​and integrated with artificial intelligence ethics (AI Ethics) as a strategic approach to transform character and digital citizenship in Indonesia. The background of this study arises from the growing ethical challenges in the digital era, such as AI misuse in the form of disinformation, data manipulation, and moral degradation, all of which threaten national identity and moral integrity. Employing a qualitative descriptive approach based on library research (conceptual and normative literature review), this study analyzes the conceptual interrelation between Pancasila values, AI ethical principles, and the paradigm of digital citizenship education through content analysis of academic literature, national education policies, and international AI ethics frameworks. The findings reveal a substantial alignment between the core principles of AI ethics, transparency, fairness, accountability, and humanity - and the foundational moral values ​​of Pancasila. Integrating these dimensions produces a conceptual model called the Ethical Digital Citizenship Framework, serving as a guide for curriculum development and character education policies in the age of artificial intelligence. Conceptually, this research contributes to enriching transformative educational discourse that bridges local moral wisdom with global ethical values ​​and offers strategic directions for shaping digital citizens who are faithful, civilized, and morally responsible in the era of intelligent technology.